1979
DOI: 10.1007/bf02663051
|View full text |Cite
|
Sign up to set email alerts
|

Removal of phytate from soy protein

Abstract: Phytate, as a minor constituent of soybeans, has been reported to interfere with the dietary mineral absorption of mammals. Commercial soy protein isolate contains 2–3% tightly bound phytate. Practifrom soy protein materials. However, in this reported process, the phytate content was reduced to extremely low levels using commercially feasible processing techniques. The first step of this process was the extraction of water soluble components from soy flakes using routine commercial procedures. In the second st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
25
0
1

Year Published

1981
1981
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 5 publications
0
25
0
1
Order By: Relevance
“…They also reported that these two steps, soaking and dehulling, decreased the levels of phytates by 4%. However, the more substantial decrease of tannins and phytates in these concentrates can be attributed to the alkaline treatment during the process of protein concentrate preparation (Hartman, 1979).…”
Section: Resultsmentioning
confidence: 99%
“…They also reported that these two steps, soaking and dehulling, decreased the levels of phytates by 4%. However, the more substantial decrease of tannins and phytates in these concentrates can be attributed to the alkaline treatment during the process of protein concentrate preparation (Hartman, 1979).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, no significant changes were found in the apparent digestibility of other nutrients following phytase supplementation. Hartman (1979) stated several decades ago that 2-3% of soyabean protein forms a very stable complex with phytate. The binding form of this complex determines the extent to which the digestibility of protein can be increased by enzyme supplementation.…”
Section: Resultsmentioning
confidence: 99%
“…Phytic acid is also known to have a strong affinity for zinc, iron, and trace minerals in foods and feeds. Its association with storage proteins results in relatively high concentrations of phytic acid in commercial soy protein products, such as soy meal, that are mainly used for swine and poultry feeds (1,2,5). The presence of phytic acid has a definite effect on the economic value and nutritional quality of the animal feeds.…”
mentioning
confidence: 99%
“…Phytic acid, myo-inositol hexaphosphate, is the principal storage form of phosphorus in soybeans (1) and is known to associate with the β-conglycinin (7S) fraction of the storage proteins (2)(3)(4). Phytic acid is also known to have a strong affinity for zinc, iron, and trace minerals in foods and feeds.…”
mentioning
confidence: 99%